Implementasi Proses Administrasi Pendidikan dalam Kurikulum Merdeka di SD IT Zia Salsabila - Azzahra, Shadrina; Nadya, Laila; Hutasuhut, Naila Audiva (TSAQOFAH, 2024)
This research discusses the implementation of educational administration in the independent curriculum at SD IT Zia Salsabila. An independent curriculum is an educational approach that gives teachers and students more freedom in developing a curriculum that suits students' needs and potential. .In this research, educational administration at SD IT Zia Salsabila is seen as an important part in implementing the independent curriculum. The research results show that effective educational administration can help improve the quality of education at SD IT Zia Salsabila. In this case, effective educational administration can help teachers develop a curriculum that suits students' needs and increase student participation in the learning process. Apart from that, effective educational administration can also help improve the quality of educational facilities and infrastructure at SD IT Zia Salsabila, so that it can improve the overall quality of education. Thus, this research shows that effective educational administration is very important in implementing the independent curriculum at SD IT Zia Salsabila and can help improve the quality of education at the school.